Inflammatory Profiles of Tracheal Biopsies From SARS-CoV-2 Patients - Fiacchini, Giacomo; Proietti, Agnese; Poma, Anello Marcello; Picariello, Miriana; Dallan, Iacopo; Guarracino, Fabio; Forfori, Francesco; Fontanini, Gabriella; Bruschini, Luca (Frontiers in Microbiology, 2022)
Purpose. An increasing number of laryngotracheal complications in mechanically ventilated COVID-19 patients has been reported in the last few months. Many etiopathogenetic hypotheses were proposed but no clear explanation of these complications was identified. In this paper we evaluated the possibility that the tracheal mucosa could be a high viral replication site that could weaken the epithelium itself. Methods. Subjects for the COVID-19 group and the control group were selected retrospectively according to specific criteria. Patients’ basic and clinical data were recorded and analyzed. Tracheal samples of both groups were collected during surgical tracheostomies and then analyzed from an histological and genetic-transcriptional point of view. Results. Four COVID-19 patients were enrolled in this study and compared with 4 non-COVID-19 patients. No laryngotracheal complications were identified in both groups. The SARS-CoV-2 was detected in one out of four COVID-19 samples. A subepithelial inflammatory lymphomonocyte infiltrate was observed in all patients but two cases of the COVID-19 group showed vasculitis of small subepithelial vessels associated with foci of coagulative necrosis. Two gene sets (HALLMARK_INFLAMMATORY_RESPONSE and HALLMARK_ESTROGEN_RESPONSE_LATE) were significantly deregulated in COVID-19 patients compared to the control group. Conclusion. The altered inflammatory response of the COVID-19 patients could be another possible explanation of the increasing number of laryngotracheal complications.